2019
DOI: 10.3390/antiox8090403
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Heme Oxygenase-1 in Remote Ischemic and Anesthetic Organ Conditioning

Abstract: The cytoprotective effects of the heme oxygenase (HO) pathway are widely acknowledged. These effects are mainly mediated by degradation of free, pro-oxidant heme and the generation of carbon monoxide (CO) and biliverdin. The underlying mechanisms of protection include anti-oxidant, anti-apoptotic, anti-inflammatory and vasodilatory properties. Upregulation of the inducible isoform HO-1 under stress conditions plays a crucial role in preventing or reducing cell damage. Therefore, modulation of the HO-1 system m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 146 publications
0
14
0
Order By: Relevance
“…It has been shown that anesthetic conditioning (AC) may attenuate the IRI process [ 11 , 12 ]. AC is safe and easy to perform and is routinely used for anesthesia in surgical patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that anesthetic conditioning (AC) may attenuate the IRI process [ 11 , 12 ]. AC is safe and easy to perform and is routinely used for anesthesia in surgical patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence shows that the administration of volatile anesthetics may offer protection against organ ischemic damage through a mechanism called anesthetic conditioning (AC) and attenuate the IRI process [ 11 , 12 ]. Based on the timing of administration, AC is defined as preconditioning (before ischemia), perconditioning (during ischemia), or postconditioning (after reperfusion).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we then tried to reveal the self-adaptive protection mechanism, which might provide a novel target to reverse endogenous repair failure and promote the development of therapies for IVD degeneration. 9 Oxidative Medicine and Cellular Longevity HO-1, which has been identified in many pathophysiological scenarios, serves a critical biological function as the rate-limiting enzyme in the metabolism of heme to generate biliverdin, carbon monoxide, and iron [30,31]. As a cellular stress protein, HO-1 can function as one of the most important factors of cell adaptation to oxidative stress and exert cytoprotective effects against environment stress-induced inflammation and cell death [32].…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase-1 (HO-1), also known as a 32 kDa heat-shock protein, is an intracellular enzyme that catalyzes the degradation of heme into biliverdin, ferrous iron, and carbon monoxide (CO), with biliverdin being subsequently catabolized into bilirubin [7][8][9][10][11]. HO-1 is highly induced in response to various stress signals, such as free heme and hemoglobin, inflammatory cytokines, ischemia, endotoxins, irradiation, and mucosal damage [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%